Motivational factors predicting ICT literacy: First evidence on the structure of an ICT motivation inventory. (May 2017) - Senkbeil, Martin; Ihme, Jan Marten
Abstract: The ability to use information and communication technologies (ICT) is essential for private and vocational participation in society. Although motivational facets play an important role in developing ICT knowledge and skills, only few studies assessing computer-related knowledge and skills present a comprehensive concept on these motivational facets. This article addresses this issue by presenting the construction and first validation of an ICT motivation inventory on the basis of social cognitive theory. The focus of this newly developed concept is to predict computer-related knowledge and skills. Its theoretically deduced dimensions of three ICT-related usage motives (instrumental, hedonic and social interaction), ICT-related selfefficacy, and ICT-related self-regulation were analyzed in a study assessing N = 323 German students between 16 and 27 years of age. Confirmatory factor analyses supported the assumed dimensional structure in the form of a hierarchical five-factor model. The reliability and construct validity of the measure were explored. As expected, the ICT motivation inventory dimensions were related to individual differences in ICT Literacy and relevant person characteristics (social background, need for cognition). Highlights: A conceptualization and measure of an ICT motivation inventory is proposed. The factors of usage motives, self-efficacy, and self-regulation were confirmed. Correlations with ICT literacy and person characteristics were as expected.